2019
DOI: 10.1080/17487870.2019.1624169
|View full text |Cite
|
Sign up to set email alerts
|

What are the prerequisites for a euro area fiscal capacity?

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden. Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen. Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…The last contribution, by Demertzis and Wolff (2020) highlights the question whether the current EMU governance structure has essentially been completed in the past decade. Specifically, their analysis looks at the institutional steps that would fix the issue of the "asymmetrical EMU" (Verdun 1996), that is, monetary union without a fiscal union (see also Howarth and Verdun 2020).…”
Section: Policy Highlightsmentioning
confidence: 99%
See 1 more Smart Citation
“…The last contribution, by Demertzis and Wolff (2020) highlights the question whether the current EMU governance structure has essentially been completed in the past decade. Specifically, their analysis looks at the institutional steps that would fix the issue of the "asymmetrical EMU" (Verdun 1996), that is, monetary union without a fiscal union (see also Howarth and Verdun 2020).…”
Section: Policy Highlightsmentioning
confidence: 99%
“…The crises also do not inform actors about how to reach decisions about the new governance structure. The finalité for EMU in Demertzis and Wolff (2020) includes fiscal union, besides monetary union and they argue that importance alone is not sufficient for reaching that end goal; hence the need for following a carefully designed sequence of steps towards a more symmetric EMU.…”
Section: Policy Highlightsmentioning
confidence: 99%
“…Assuming that without a fiscal union the monetary union is incomplete, Demertzis and Wolff [2016] postulate three steps to achieve more centralized budget functions in the euro area. The adoption of each of these three steps should be preceded by the fulfillment of certain preconditions.…”
Section: Fiscal Transfers Between the Euro Area Countriesmentioning
confidence: 99%
“…Fiscal capacity building and investment initiatives into European infrastructure, research and development, climate, energy, migration, and security have therefore been suggested. In addition, it has been argued, that large scale investment projects in this direction may also be used for cyclical stabilization in the euro area (Demertzis and Wolff ). In fact, Benassy‐Quere, Ragot, and Wolff () point out those discretionary fiscal policies have been pro‐cyclical on average in the euro area between 1995 and 2008.…”
Section: Introductionmentioning
confidence: 99%